1985
DOI: 10.1161/01.str.16.6.980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol on platelet aggregation in cerebral microvessels of mice.

Abstract: SUMMARY Mice were implanted subcutaneously with a pellet containing 0.5 mg estradiol or with a placebo. Eight to 12 days later platelet aggregation was produced in pial arterioles by injuring their endothelium in vivo with a noxious light/dye stimulus. The time between the onset of the noxious stimulus and the appearance of platelet aggregates was significantly shortened (p < .02) by estradiol treatment in young (2 month old) mice. The same treatment had the opposite effect in 4-6 month old mice and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A study published in 1985 has shown that mice treated by an estrogen pellet containing 0.5 mg of E2 and then submitted to a mesenteric endothelial injury exhibited a faster thrombosis response compared to the placebo group [33]. Similar results were found after a cerebral vessels injury induced by a noxious light/dye stimulus [34]. In contrast, we recently reported that a three-week high dose of E2 (200 μg/kg/day) treatment increased the tail-bleeding time, and protected animals against collagen/epinephrine-induced thromboembolism, and against injury-induced carotid artery thrombosis compared to ovariectomized or sham-operated mice [24].…”
Section: Effects Of Estrogen Treatment On Platelet Activationmentioning
confidence: 73%
“…A study published in 1985 has shown that mice treated by an estrogen pellet containing 0.5 mg of E2 and then submitted to a mesenteric endothelial injury exhibited a faster thrombosis response compared to the placebo group [33]. Similar results were found after a cerebral vessels injury induced by a noxious light/dye stimulus [34]. In contrast, we recently reported that a three-week high dose of E2 (200 μg/kg/day) treatment increased the tail-bleeding time, and protected animals against collagen/epinephrine-induced thromboembolism, and against injury-induced carotid artery thrombosis compared to ovariectomized or sham-operated mice [24].…”
Section: Effects Of Estrogen Treatment On Platelet Activationmentioning
confidence: 73%
“…Female C57Bl/6 mice were divided into five groups (n ϭ 5-13 per group) that received 17␤-estradiol alone (0.5 mg/pellet) or with tamoxifen (5 mg/pellet), tamoxifen alone (5 mg/pellet), 17␣-estradiol (0.5 mg/pellet), or placebo via 21-day release pellets implanted subcutaneously (IRA, Sarasota, Florida). The dose of 17␤-estradiol used in this study markedly elevates the plasma hormone level in mice (ϳ1,000 pg/ml) by 7 days after implantation, and these levels remain constant for 4 wk (49,50).…”
Section: Dnb Colitismentioning
confidence: 76%
“…Estrogens: Fall in premenstrual levels; 110,202,203 oral anticonceptives; 204,205 hormonal replacement therapy 121…”
Section: -Migraine Provoking Triggers That Increase Platelet Aggregabmentioning
confidence: 99%